FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Ronny, Tony Sudirgo (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of profitability, Investment Opportunity Set (IOS), leverage, dividend policy, and Earning Per Share (EPS) on firm value in manufacturing industries listed in Indonesian Stock Exchange during the period of 2015-2017. This research used 42 samples of manufacturing companies that have been previously selected using purposive sampling method for three years of a total population of 155 manufacturing companies. The data used were secondary data in the form of financial information from the financial statements and annual reports. This research data was processed using EViews 9. The result of this research shows that profitability and Investment Opportunity Set (IOS) has a significant effect on firm value, while leverage, dividend policy, and Earning Per Share (EPS) does not have a significant effect on firm value.